2021
DOI: 10.1200/op.21.00269
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Patients' Perspectives on Remote Patient Monitoring for COVID-19

Abstract: PURPOSE: Oncology patients are vulnerable to adverse outcomes associated with COVID-19, and clinical deterioration must be identified early. Several institutions launched remote patient monitoring programs (RPMPs) to care for patients with COVID-19. We describe patients' perspectives on a COVID-19 RPMP at a National Comprehensive Cancer Center. METHODS: Patients who tested positive for COVID-19 were eligible. Enrolled patients received a daily electronic COVID-19 symptom assessment, and a subset of high-risk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Even if participants’ views seemed to grow more positive over time, they emphasized both positive and negative effects of the remote monitoring. Studies have shown that cancer patients appreciate that remote monitoring provides information and a clinical safety net, also being a link to the nurses and physicians during a period of isolation [ 17 , 32 , 33 ]. Technological barriers, such as software defects, access to video-compatible devices, access to high-speed internet, and individual technological fluency has been associated with decreased satisfaction [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if participants’ views seemed to grow more positive over time, they emphasized both positive and negative effects of the remote monitoring. Studies have shown that cancer patients appreciate that remote monitoring provides information and a clinical safety net, also being a link to the nurses and physicians during a period of isolation [ 17 , 32 , 33 ]. Technological barriers, such as software defects, access to video-compatible devices, access to high-speed internet, and individual technological fluency has been associated with decreased satisfaction [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview guide was developed based on previous research on cancer patients’ experiences with remote monitoring e.g. [ 17 , 18 ], and through several discussions within the research group until consensus was reached (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high level of patient acceptance has been previously reported by other studies who have described excellent patient satisfaction with virtual care during the COVID-19 pandemic. 2,[19][20][21][22][23] Aside from the near ubiquitous symptom of cough, dyspnoea was the symptom most frequently identified within the hypoxic group and thus patients reporting dyspnoea as a prominent symptom of their COVID-19 symptom profile should have access to home pulse oximetry. Conversely, cough in the absence of other respiratory symptoms was not a useful predictor of clinical deterioration, hypoxia and escalation to an ED.…”
Section: Discussionmentioning
confidence: 99%
“…ePRO data were evaluated from October 16, 2018, to February 29, 2020; this cutoff was chosen owing to program changes after this date caused by the COVID-19 pandemic. 27 , 28 The total number of assessments generating alerts and alert severity (red or yellow) by symptom were quantified.…”
Section: Methodsmentioning
confidence: 99%